seismic stratigraphy of the fang basin, Chiang Mai, Thailand - Rungsun Nuntajun (2018)
The Fang Basin is located about 150 km northwest of Chiang Mai. Based on characteristics of reflection seismic data, the Cenozoic sediment in the centre of the basin can be subdivided into 7 units (Sequences 1-7), which have been interpreted as being deposited in fluvial and lacustrine environments. These basin fills are underlain by Pre-Tertiary basement comprising weathered andesite and Permian limestone. Sequence 1 represents the initial deposition during the opening of the basin. The top of the sequence is marked by bituminous shale and lignite in the eastern part of the basin. These strata have been regarded as good source rocks for the oil fields in the area. Sequence 2 is a west-directed prograding succession of sandstone interbedded with shale. Sequence 3 has been interpreted to represent a transition in depositional regime from sand-dominated fluvial to mud-dominated lacustrine environments. The upper boundary of the sequence is marked by a coal layer indicating a period of low energy and wet conditions. Sequence 4 consists of a prograding succession of sandstone and shale, representing a change in depositional environment to one of higher energy than that of Sequence 3. Sequence 5 comprises sand-dominated strata at the basin margins that grade into mud-dominated strata in the basin centre. Most reservoirs in the Fang oil fields are located within Sequence 5. Sequence 6 consists largely of shale with minor sand interbeds. Sequence 6 is unconformably overlain by Sequence 7, composed of interbedded sandstone and shale. Based on the architecture of the sedimentary layers and distribution of sediment types, it has been interpreted that the basin fills were supplied from the western and eastern margins of the basin.